The Importance of Human Resource Development and Job Satisfaction at Sekar Bengawan Limited Liability Company - Adipramana, Silva; Alfadhilla, Dina Amalia; Saraswati, Laila Isnaini (LPPM STIAB Jinarakkhita Lampung, 2024)
Human resource development is a key strategy undertaken by companies to improve production output and productivity. In the context of Sekar Bengawan Solo Limited Liability Company, employee job satisfaction is a critical factor in achieving this goal. Job satisfaction can be obtained when the employee feels that what they have contributed to the company is well received. This study aims to understand the relationship between human resource development and job satisfaction on employee performance in the company. Through a qualitative approach, this study used interviews and observation methods to explore employees' views and identify patterns in the practice of human resource development and job satisfaction at Perusahaan Terbatas Sekar Bengawan Solo. The results show that influences in human resource development, such as training and skills development, directly affect employee job satisfaction. Employee job satisfaction depends not only on financial aspects, but also on recognition, learning, and a supportive work environment. Therefore, continuous efforts are needed to strengthen human resource development programs in this company. With increased job satisfaction, it is expected that employee performance will be optimized, providing a positive impact on the company in achieving production goals and sustainable growth.